Redox Status of Erythrocytes as an Important Factor in Eryptosis and Erythronecroptosis - Tkachenko, Anton; Havránek, Ondřej (Folia biologica, 2023)
Overall, reactive oxygen species (ROS) signalling significantly contributes to initiation and mo-dulation of multiple regulated cell death (RCD) pathways. Lately, more information has become available about RCD modalities of erythrocytes, including the role of ROS. ROS accumulation has therefore been increasingly recognized as a critical factor involved in eryptosis (apoptosis of erythrocytes) and erythro-necroptosis (necroptosis of erythrocytes). Eryptosis is a Ca2+-dependent apoptosis-like RCD of erythrocytes that occurs in response to oxidative stress, hyperosmolarity, ATP depletion, and a wide range of xenobiotics. Moreover, eryptosis seems to be involved in the pathogenesis of multiple human diseases and pathological processes. Several studies have reported that erythrocytes can also undergo necroptosis, a lytic RIPK1/RIPK3/MLKL-mediated RCD. As an example, erythronecroptosis can occur in response to CD59-specific pore-forming toxins. We have systematically summarized available studies regarding the involvement of ROS and oxidative stress in these two distinct RCDs of erythrocytes. We have focused specifically on cellular signalling pathways involved in ROS-mediated cell death decisions in erythrocytes. Furthermore, we have summarized dysregulation of related erythrocytic antioxidant defence systems. The general concept of the ROS role in eryptotic and necroptotic cell death pathways in erythrocytes seems to be established. However, further studies are required to uncover the complex role of ROS in the crosstalk and interplay between the survival and RCDs of erythrocytes.
Keywords: erythronecroptosis; damage-associated molecular patterns; Calcium; RCD; regulated cell death; reaktivní formy kyslíku; vápník; ROS; hydrogen peroxide; oxidace-redukce; Reactive Oxygen Species; eryptóza; erythrocytes; lidé; Eryptosis; Humans; eryptosis; erytrocyty; Erythrocytes; DAMPs; apoptosis; Oxidation-Reduction; reactive oxygen species; necroptosis